Research of Key Technologies on Encrypting Vector Spatial Data in Oracle Spatial - Guangshi Li (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
This paper expatiates on the research status of encrypting spatial data in recently years, and analyzes the organizational structure of vector spatial data in Oracle Spatial. Aiming at the disadvantage of Oracle data encryption mechanism and security hidden danger of the spatial data storage, a spatial data encryption system based on external DBMS is designed. The research also introduces the main functions of Spatial Data Encryption Engine (SDEE), which is the core components of encryption system. The paper focuses on several key problems that need to be considered during the design process, including choice of spatial data encryption algorithm and encryption granularity, key management methods and encryption method of R-tree spatial index. In order to solve these problems ,the corresponding solutions are presented.